Mass Fragmentation Pattern of Some Mono- and Di-Substituted Formamidines. Part-1. Mass Pattern of 1-Arylformamidines (Biological Sciences - PJSIR, 2005)
Some 1-arylformamidines were prepared by the Raney nickel (W-2) desulphuration of some 1-arylthioureas in anhydrous boiling benzene medium. Mass fragmentation patterns of the products were ascertained from the mass spectral data.